Aproveitamento do caroço do açaí como substrato para a produção de enzimas por fermentação em estado sólido - Santos, Rodrigo Rafael Mendonça dos (2010)
The açaí agroindustry is the most important productive chains in northern Brazil. The residues in the marketing of açaí consists mainly of its pits, which are discarded in landfills and waterways without any treatment. A possible application to açaí pits is its use as substrate for solid state fermentation (SSF) for the production of lignocellulolytic enzymes as CMCase and xylanase, which act in the conversion of lignocellulosic materials into fermentable sugars. Currently, the cost of production of these enzymes has emerged as the biggest obstacle to the use of agro-industrial waste and the process of SSF gained prominence in this context due to several advantages over other technologies. The SSF process presents a large number of variables that affect the production of metabolites of interest, highlighting the sources of carbon and nitrogen, inducing growth and mineral salts. This study aimed to evaluate the use of pits of açaí as substrate for enzyme production by SSF evaluating the influence of the composition of culture medium for SSF through application of the methodology of statistical design full factorial 24 for selection of significant variables. The variables studied were the initial medium moisture and the concentrations of meat peptone extract, yeast extract, and CMC. After extraction of the enzyme complex and quantification of CMCase and xylanase activities, the variables of concentration of meat peptone extract and yeast extract were significant for enzyme production. Subsequently, a central composite rotatable design (CCRD) was made to achieve the optimization of the process parameters. The highest activities were obtained by increasing the concentration of meat peptone extract and yeast extract, reaching 8.24 U g-1 and 8.08 U g-1, to CMCase and xylanase, values, respectively. Additional tests were made at concentrations three times higher than those used at the midpoint of the CCRD, which indicated an increase of 1.59 and 1.16 times in the enzymatic activities of CMCase and xylanase, respectively. However, by Tukey test, these increases did not differ statistically in comparison to the tests results obtained using concentrations of reagents encoded at +1.41, giving economic advantage to the tests made with smaller amounts of reagents. The pit of açai has shown promising as a substrate for SSF, but additional studies are performed to define and optimize the process parameters.